Social Support with Multiple Role Conflicts of Women Teachers During the Pandemic - Wahyu Retno ningsih, Shavira Ayu; Rahayu, Diah; Adriansyah, Muhammad Ali (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Online learning during a pandemi is a recommended alternative This condition requires them to work at home not only teaching students but also carrying out the role of wife and babysitter at home. This is what creates conditions that lead to multiple role conflict. Women who experience multiple role conflicts really need social support from their surroundings, be it support from their husbands or those closest to them. This study aims to determine the relationship between social support and the dual role conflict of female teachers during a pandemi. This quantitative research was conducted on 131 female teachers through a purposive sampling technique. The measuring instrument used is the multiple role conflict scale and social support. The results of this study found that the higher the social support, the lower the dual role conflict experienced by female teachers. The implications of the results of this study indicate that dual role conflicts for female teachers who teach Online at home and are faced with other responsibilities can be overcome by providing support to women in carrying out their roles.Pembelajaran daring di masa pandemi menjadi alternatif yang direkomendasikan Kondisi ini mengharuskan mereka bekerja di rumah tidak hanya mengajar siswa tetapi juga menjalankan peran sebagai istri dan babysitter di rumah. Inilah yang menciptakan kondisi yang menyebabkan konflik peran ganda. Perempuan yang mengalami konflik peran ganda sangat membutuhkan dukungan sosial dari sekitarnya, baik itu dukungan dari suami maupun orang-orang terdekatnya. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dan konflik peran ganda guru perempuan di masa pandemi. Penelitian kuantitatif ini dilakukan terhadap 131 guru perempuan melalui teknik purposive sampling. Alat ukur yang digunakan adalah skala konflik peran ganda dan dukungan sosial. Hasil penelitian ini menemukan bahwa semakin tinggi dukungan sosial, semakin rendah konflik peran ganda yang dialami guru perempuan. Implikasi dari hasil penelitian ini menunjukkan bahwa konflik peran ganda bagi guru perempuan yang mengajar secara daring di rumah dan dihadapkan pada tanggung jawab lain dapat diatasi dengan memberikan dukungan kepada perempuan dalam menjalankan perannya.